2005
DOI: 10.2139/ssrn.852684
|View full text |Cite
|
Sign up to set email alerts
|

Currency Crisis, Monetary Policy, and Corporate Balance Sheet Vulnerabilities

Abstract: and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commercial gain • You may freely distribute the URL identifying the publication in the public portal Take down policy If you believe that this document breaches co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2007
2007
2007
2007

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The following model was used by Eijffinger and Goderis (2005) to study the empirical impact of monetary policy on the exchange rate:…”
Section: Annex B: Monetary Policy and Financial Crisesmentioning
confidence: 99%
See 2 more Smart Citations
“…The following model was used by Eijffinger and Goderis (2005) to study the empirical impact of monetary policy on the exchange rate:…”
Section: Annex B: Monetary Policy and Financial Crisesmentioning
confidence: 99%
“…Eijffinger and Goderis (2005) focused on debt levels, whereby they have estimated the marginal impact of monetary policy for different levels of corporate debt. They concluded that the impact of monetary policy depends on the ratio short-term corporate debt to assets.…”
Section: Annex B: Monetary Policy and Financial Crisesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, when debt levels are taken into account, a clearer picture emerges. Eijffinger and Goderis (2005) show that the impact of monetary policy on the exchange rate is non-linear and non-monotonic. They find that for relatively low corporate debt levels (i.e.…”
mentioning
confidence: 99%